Paradigma Integratif-Interkonektif M. Amin Abdullah; Telaah Hermeneutika al-Quran dalam Konteks Keilmuan Interdisipliner - Isrha, Muhammad; A, Arsihannor,; Latif, Muhaemin (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article examines the integrative–interconnective paradigm developed by M. Amin Abdullah as an epistemological framework for the development of Qur’anic hermeneutics amid the growing prominence of interdisciplinary approaches in scholarship. The study departs from the problem of the dichotomy between normative Islamic sciences and the social–humanities sciences, which has long influenced methods of Qur’anic interpretation, often resulting either in ahistorical textual readings or, conversely, contextual approaches that lose their normative grounding. Employing a qualitative approach through critical library research, this study analyzes Amin Abdullah’s key ideas on the integration and interconnection of knowledge and their relevance to the development of contemporary Qur’anic hermeneutics. The findings indicate that Amin Abdullah’s integrative–interconnective paradigm offers a hermeneutical model that positions the Qur’an as a normative text continuously engaged in dialogue with historical, social, and cultural contexts. This approach creates space for the utilization of various disciplines—such as linguistics, history, sociology, and anthropology—without negating the authority of the revealed text. Within an interdisciplinary scholarly context, this paradigm functions as a methodological bridge for addressing the complexity of modern Muslim issues in a more comprehensive and responsible manner.